Sensory Qualities of Oysters Unaltered by a Short Exposure to Combined Elevated pCO2 and Temperature - Lemasson, Anaëlle J.; Kuri, Victor; Hall-Spencer, Jason M.; Fletcher, Stephen; Moate, Roy; Knights, Antony M. (Frontiers in Marine Science, 2017)
Reliance on the marine environment for the provision of food is ever-increasing, but future climate change threatens production. Despite this concern, the impact on seafood quality and success of the seafood industry is unknown. Using a short-term study, we test these concerns using a major aquaculture species – Crassostrea gigas – exposing them to three acidification and warming scenarios: 1) ambient pCO2 (~400 ppm) & control temperature (15°C) 2) ambient pCO2 (~400 ppm) & elevated temperature (20°C), 3) elevated pCO2 (~1000 ppm) & elevated temperature (20°C). Oyster quality was assessed by scoring appearance, aroma, taste, and overall acceptability. A panel of five experts was asked to score nine oysters – three from each treatment – according to agreed criteria. Results indicate that these levels of acidification and warming did not significantly alter the sensory properties of C. gigas, and notably the overall acceptability remained unchanged. Non-statistically supported trends suggest that several sensory attributes – opacity, mouthfeel, aspect of meat, shininess, meat resistance, meat texture, and creaminess – may improve under acidification and warming scenarios. These findings can be considered positive for the future of the aquaculture and food sectors. Crassostrea gigas therefore is expected to remain a key species for food security that is resilient to climate change, whilst retaining its valuable attributes.